2015
DOI: 10.1039/c5sc03013g
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic C–F alkylation; facile access to multifluorinated arenes

Abstract: From the top down; access to complex multifluorinated arenes via multiple photocatalytic C–F substitutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
72
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(72 citation statements)
references
References 60 publications
0
72
0
Order By: Relevance
“…7, 9, 12 Although many of the spectra match experiment, two of the structures had large errors (Chart 3, red). Based on the correction described above, revised structures were tested and these match the experimental values within the error expected for our scaling factors.…”
Section: Resultsmentioning
confidence: 99%
“…7, 9, 12 Although many of the spectra match experiment, two of the structures had large errors (Chart 3, red). Based on the correction described above, revised structures were tested and these match the experimental values within the error expected for our scaling factors.…”
Section: Resultsmentioning
confidence: 99%
“…Our group 1,39 has routinely used 3 in our standard catalyst screen, and likewise Ooi and coworkers 40 synthesized this catalyst in their asymmetric α-coupling of N -arylaminomethanes and used the photocatalyst in their optimization experiments. 3 is thus included in order to provide electrochemical and photophysical data.…”
Section: Photocatalyst Detailsmentioning
confidence: 99%
“…14 Historically these complexes have been primarily employed in solar cells, 5 light emitting diodes (LEDs), 6 and as initiators in free radical polymerizations. 7 Both of the prototypical complexes, Ru(bpy) 32+ and Ir(ppy) 3 are d 6 , coordinatively saturated, 18-electron complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Returning to the problem of multifluorinated arenes, we have previously demonstrated that the perfluoroaryl radical is a powerful intermediate for the functionalization of perfluoroarenes, which can elicit C–F alkylation, 16 arylation, 17 and alkenylation. 18 While the perfluoroaryl radical has proven competent for cross-coupling, the inherent limitation is the regioselectivity of the C–F fragmentation event.…”
Section: Introductionmentioning
confidence: 99%